Molecular dissection of connected rice populations revealed important genomic regions for agronomic and biofortification traits - Palanog, Alvin D.; Nha, Chau Thanh; Descalsota-Empleo, Gwen Iris L.; Calayugan, Mark Ian; Swe, Zin Mar; Amparado, Amery; Inabangan-Asilo, Mary Ann; Hernandez, Jose E.; Sta. Cruz, Pompe C.; Borromeo, Teresita H.; Lalusin, Antonio G.; Mauleon, Ramil; et al. (Frontiers in Plant Science, 2023)
Breeding staple crops with increased micronutrient concentration is a sustainable approach to address micronutrient malnutrition. We carried out Multi-Cross QTL analysis and Inclusive Composite Interval Mapping for 11 agronomic, yield and biofortification traits using four connected RILs populations of rice. Overall, 156 QTL were detected for agronomic (115) and biofortification (41) traits, which were higher in number but smaller in effects compared to single population analysis. The MC-QTL analysis was able to detect important QTLs viz: qZn5.2, qFe7.1, qGY10.1, qDF7.1, qPH1.1, qNT4.1, qPT4.1, qPL1.2, qTGW5.1, qGL3.1, and qGW6.1, which can be used in rice genomics assisted breeding. A major QTL (qZn5.2) for grain Zn concentration has been detected on chromosome 5 that accounted for 13% of R2. It has also identified 26 co-located QTLs that shared common SNPs. qPH6.1 epistatically interacted with qZn5.1 and qGY6.2. Most of QTLs were co-located with functionally related candidate genes indicating the accuracy of QTL mapping. The genomic region of qZn5.2 was co-located with putative genes such as OsZIP5, OsZIP9, and LOC_OS05G40490 that are involved in Zn uptake. These genes included polymorphic functional SNPs, and their promoter regions were enriched with cis-regulatory elements involved in plant growth and development, and biotic and abiotic stress tolerance. Major effect QTL identified for biofortification and agronomic traits can be utilized in breeding for Zn biofortified rice varieties.